Skizofrenia - Ridho Akbar Syafwan (Lembaga Pengembangan Kinerja Dosen, 2025)
Schizophrenia is a complex psychiatric disorder, characterized by positive, negative, and significant cognitive impairment, and contributes significantly to global disability. This article is a literature review that comprehensively discusses the epidemiology, etiology, clinical features, diagnosis, and management of schizophrenia. The etiology of schizophrenia involves interactions between genetic, neurobiological, and environmental factors, including dysfunction of neurotransmitters such as dopamine, glutamate, and gaba. Diagnosis can be made based on the criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) or the Guidelines for the Classification of Mental Disorder Diagnosis III (PPDGJ III), with an emphasis on the combination of major symptoms and the exclusion of other conditions. Management of Schizophrenia Includes Pharmacological Therapy With First and Second Generation Antipsychotics, As Well As Nonpharmacological Interventions Such As Cognitive-Behavioral Therapy, Social Skills Training, And Family Support. The Social Stigma And Economic Burden That Accompanies It Makes This Disorder A Multidimensional Challenge In The Health System. This Article Emphasizes The Importance Of A Sustained Multidisciplinary Approach To Improve The Prognosis And Quality Of Life Of People With Schizophrenia.